Design and implementation of VR lato-lato STEAM in engineering education science - Rahman Hakim, Septian; Hariyanto, Didik; Suprapto, Nadi; Yulkifli, Yulkifli; Zul Fahmi, Hafizhuddin; Nisa, Khoirun; Ainur Rizki, Iqbal (Institute of Advanced Engineering and Science, 2025)
This research focuses on integrating science, technology, engineering, art, and mathematics (STEAM) and virtual reality (VR) in engineering-science education through a lato-lato game (clackers ball). The research analyzes the development trends of VR, particularly the integration of the lato-lato game in STEAM education. Using a waterfall model, the research develops and tests VR-STEAM applications, involving analysis, design, development, and testing phases, with expert validation and student implementation. Data was collected from 60 Indonesian university students and analyzed using partial least squares structural equation modeling (PLS-SEM). Over the past 5 years, VR in education has surged, enhancing learning outcomes and student engagement. The study shows that integrating technology and pedagogy is crucial for effective STEAM education. The design of VR-STEAM is validated and ready for use. PLS-SEM analysis indicates that the indicators are valid and reliable for measuring university students’ experiences. The study reveals that integrating STEAM with VR significantly enhances engineering-science learning (ESL), focusing on understanding, personal goals, communication, and cooperation. VR serves as a mediator that fosters 21st-century skills. The research recommends developing assessment tools to measure VR-STEAM ethnoscience and evaluate effectiveness, highlighting the importance of technology in improving learning and connecting concepts to real-world phenomena like lato-lato.